2021
DOI: 10.1017/s0016756821001126
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of upper Palaeozoic ‘thin-layer’ limestones in the southern North China Craton: implications for closure of the northeastern Palaeotethys Ocean

Abstract: During the late Palaeozoic Era, a series of related marine strata dominated by multi-layer limestones were deposited in the southern North China Craton. In order to gain new insights into the systematic geochemistry of the carbonate succession of the representative formation (Taiyuan Formation), we examined 59 limestone samples collected from the Huaibei Coal Basin (HCB), with a view towards quantitatively determining the major and trace elements and stable isotope compositions. The data obtained can provide e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 94 publications
1
1
0
Order By: Relevance
“…Hydrothermal alteration and burial metamorphic can occur during the early and late stages of diagenesis, leading to the destruction of the original depositional information in carbonate rocks (Knauth & Kennedy, 2009;Li et al, 2022). The findings of our chemical analyses of major oxides in the present study revealed that calcite is the main mineral component of limestones of the Govanda Formation, which is consistent with the average content of CaO (51.6%).…”
Section: Evaluation Of Diagenetic Alterationsupporting
confidence: 86%
See 1 more Smart Citation
“…Hydrothermal alteration and burial metamorphic can occur during the early and late stages of diagenesis, leading to the destruction of the original depositional information in carbonate rocks (Knauth & Kennedy, 2009;Li et al, 2022). The findings of our chemical analyses of major oxides in the present study revealed that calcite is the main mineral component of limestones of the Govanda Formation, which is consistent with the average content of CaO (51.6%).…”
Section: Evaluation Of Diagenetic Alterationsupporting
confidence: 86%
“…REEs patterns in carbonate rocks are not affected by alteration or strong weathering (Webb & Kamber, 2000). However, the behavior of certain elements, such as Ce and Eu, may vary due to differences in valence states under different redox conditions, leading to anomalies in their behavior and differentiation in rare earth element associations (Webb & Kamber, 2000;Tribovillard et al 2006;Li et al 2022). According to Webb & Kamber (2000), in this study, we assessed the correlations between Ce/Ce*;…”
Section: Evaluation Of Diagenetic Alterationmentioning
confidence: 99%